Pengaruh Partisipasi Masyarakat Terhadap Realisasi Anggaran Program Inovasi Pembangunan dan Pemberdayaan Kewilayahan Kota Bandung - Suhari Ramdani; Mubarok Mubarok (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2020)
This journal discusses the influence of public participation on the realization of the budget of the Development Innovation Program and the Empowerment of the Area in the District of Bojongloa Kidul, Bandung. This research is important to do because the percentage of budget realization of PIPPK in Bojongloa Kidul sub-district is very high in the last four years where the high budget realization of the program must be in line with the participation of the people in the region. The theory used in this research is the theory of community participation from Cohen&Uphoff (1980) which discusses funding for community participation in planning, implementation, utilization, and evaluation and budget realization theory from Indra Bastian, which discusses optimal budget realization (2010). The research method in this research is a quantitative associative research method which means that this study is intended to find out the clear relationship between Community Participation and Realization of PIPPK Budget with data and analysis that uses a lot of numbers. The results of this study indicate that the influence exerted by Community Participation on the realization of the PIPPK budget is 0.856 (85.6%) and falls under the very high influence criteria. Thus it can be concluded that there is a very high influence of Community Participation on the realization of the PIPPK budget in Bojongloa Kidul District, Bandung City. This shows that community participation has an important role in the success of the Regional Development and Empowerment Innovation Program in the District of Bojongloa Kidul, Bandung.